"A Regiment of Skeletons and an Army of Bottles": Reading the Hunterian Museum in Nineteenth-Century Scientific and Popular Culture - Burke, Verity (Romanticism on the Net, 2018)
Closely associated with, and used as a demonstration of the professionalization of medicine, anatomy museums and the bodies they displayed were troubled by associations ranging from the outmoded cabinet of curiosity to quackery. The myriad publications produced by educational anatomy museums foregrounded an ambition to make museums a scientific space, and the human and animal body a scientific subject through material and textual ordering. They intended to educate by placing objects in series that told a specific story, by taxonomising and cataloguing, lecturing and labelling, pinning knowledge both to the body’s material form, and the texts that illuminated it. This use of narrative was not a one-way adoption of literary techniques to legitimize institutions; literary culture frequently borrowed the ordering principles of the museum, mediating both the popular understanding of museum spaces, and the potentially sensational representation of bodies in reportage and fiction. This paper reads the catalogues, guidebooks and specimen representations of the Hunterian Museum in the Royal College of Surgeons, England, alongside its representation in Charles Dickens’s popular periodical Household Words to consider how knowledge is hermeneutically constructed, legitimizing anatomical intermediality and the museum project.